Machaut's Mass: An Introduction - Leech-Wilkinson, Daniel (Oxford Clarendon, 1992)
One of the most widely studied and performed works of music written before 1600, Machaut's Messe de Notre Dame stands as an enduring monument of medieval musical art. The mass itself, however, is surrounded by uncertainty; its date of composition remains unknown, its purpose is unclear, and its construction yields much ambiguity. A controversial new approach to Machaut's composition technique, this volume provides a case study in the application of music ficta and a detailed introduction to performance. Relating the Mass to other works of the period, this introduction is an invaluable guide to its intricacies.
Keywords: Machaut, Guillaume de -- c. 1300-1377; Notre-Dame de Paris (France); Middle Ages (500-1400); Mass; Catholicism; Polyphony; Paris (France)